Human milk oligosaccharides differentially support gut barrier integrity and enhance Th1 and Th17 cell effector responses in vitro - Boll, Erik Juncker; Lopez, Daniel Villalba; Terne, Mandy; Hessing, Sara; Parschat, Katja; Jensen, Stina Rikke (Frontiers in Immunology, 2024)
Human milk oligosaccharides (HMOs) can modulate the intestinal barrier and regulate immune cells to favor the maturation of the infant intestinal tract and immune system, but the precise functions of individual HMOs are unclear. To determine the structure-dependent effects of individual HMOs (representing different structural classes) on the intestinal epithelium as well as innate and adaptive immune cells, we assessed fucosylated (2′FL and 3FL), sialylated (3′SL and 6′SL) and neutral non-fucosylated (LNT and LNT2) HMOs for their ability to support intestinal barrier integrity, to stimulate the secretion of chemokines from intestinal epithelial cells, and to modulate cytokine release from LPS-activated dendritic cells (DCs), M1 macrophages (MØs), and co-cultures with naïve CD4 + T cells. The fucosylated and neutral non-fucosylated HMOs increased barrier integrity and protected the barrier following an inflammatory insult but exerted minimal immunomodulatory activity. The sialylated HMOs enhanced the secretion of CXCL10, CCL20 and CXCL8 from intestinal epithelial cells, promoted the secretion of several cytokines (including IL-10, IL-12p70 and IL-23) from LPS-activated DCs and M1 MØs, and increased the secretion of IFN-γ and IL-17A from CD4 + T cells primed by LPS-activated DCs and MØs while reducing the secretion of IL-13. Thus, 3′SL and 6′SL supported Th1 and Th17 responses while reducing Th2 responses. Collectively, our data show that HMOs exert structure-dependent effects on the intestinal epithelium and possess immunomodulatory properties that confer benefits to infants and possibly also later in life.